Strategi Pelayanan Misi Gereja di Era Digital dan Integrasi Terhadap Generasi Zillenial - Jaya Hia, Lurusman (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2023)
The challenge of the church with digital developments in the 20th century has amazed many church communities difficult to adapt to technological developments, especially in doing evangelism. Although there are churches that have begun to adapt to technology, it cannot be denied that there are still churches that still cannot keep up with its development in acting to preach the gospel to the congregation, and especially for young people or often called the zillennial generation (Gen Z) through social media. Ironically, technology is more interesting to Gen Z than theology today. Therefore, the purpose of this article is to offer an ideology about the essentials of the church and efforts to carry out evangelistic missions in the digital era. The result of this research is that the church can be clearly understood in the digital era and is able to do mission through the church's social media with the aim of not reaching people who do not know the church, but reaching people who do not know the true Christian faith. So that the responsibility of the church can be successful by carrying out the mission of preaching the gospel in the digital era along with its development.